2010
DOI: 10.1007/s10113-010-0179-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and agricultural vulnerability: a case study of rain-fed wheat in Kairouan, Central Tunisia

Abstract: In the Maghreb and North African regions, the interannual climate variability causes severe impacts on agriculture through long drought episodes. Impacts are expected to increase due to projected climate change. Decreasing water availability will have a direct impact on the agriculture sector and could endanger the socioeconomic development and social stability in Tunisia where rain-fed agriculture represents the main occupancy and means of subsistence for the large rural population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 4 publications
(3 reference statements)
0
21
0
1
Order By: Relevance
“…South Asia (Lal 2010;Mirza 2010), Sahelian and northern Africa (Sissoko et al 2010), Ben Mohamed (2010), Mougou et al (2010), Iglesias et al (2010) and parts of Russia (Dronin and Kirilenko 2010) by the time global mean warming reaches around 2°C above preindustrial. Lal (2010) shows that India needs to increase its production by 1.5% per year to feed its developing and growing population, faster than historical experience, but faces likely net cereal production losses in South Asia due to climate change of 4-10% for a 2°C warming.…”
Section: Food Productionmentioning
confidence: 99%
“…South Asia (Lal 2010;Mirza 2010), Sahelian and northern Africa (Sissoko et al 2010), Ben Mohamed (2010), Mougou et al (2010), Iglesias et al (2010) and parts of Russia (Dronin and Kirilenko 2010) by the time global mean warming reaches around 2°C above preindustrial. Lal (2010) shows that India needs to increase its production by 1.5% per year to feed its developing and growing population, faster than historical experience, but faces likely net cereal production losses in South Asia due to climate change of 4-10% for a 2°C warming.…”
Section: Food Productionmentioning
confidence: 99%
“…Lhomme et al (2009) simulated durum wheat production under climate change conditions for two regions: Jendouba and Kairouan, respectively situated in the north and the center of Tunisia; they are characterized by a typical Mediterranean climate. Mougou et al (2011) assessed the impact of projected climate change on wheat yield and the wheat growing season duration using the IPCC, 2001 scenarios of temperature increase: IS92c (11.3 C), IS92a (12 C), IS92e (12.5 C), and (14 C). A simple crop model was used for the simulation of the 2071À2100 climate projection.…”
Section: The Impact Of Climate Change On Wheat Production In Tunisia'mentioning
confidence: 99%
“…The impact of climate change on wheat production has been evaluated with the Decision Support System for Agrotechnology Transfer (DSSAT) crop model using previous simulation findings. However, Mougou et al (2011) showed that in the Kairouan region, when applying the scenario of combined effect of temperature increase (11.5 C) and rainfall decrease (210%), wheat production can fall by 248%. Lhomme et al (2009) showed probable decreases in crop productivity in Jendouba (northern region with semiarid climate) but an increase in Kairouan (the center region with arid climate).…”
Section: The Impact Of Climate Change On Wheat Production In Tunisia'mentioning
confidence: 99%
See 1 more Smart Citation
“…The northwest Maghreb (Morocco, Algeria and Tunisia) is critically dependent on climate because the main occupation of their populace is subsistence agriculture, so any increase in rainfall variability could seriously affect whole countries (Mougou et al 2011). The knowledge of the present climate and the pro-jected changes is crucial to aid in the modifications that will be needed to help the agricultural system adapt (Rosenberg 1992).…”
Section: Introductionmentioning
confidence: 99%